Tax Application Analysis Addition Mark (PPN) at PT Perkebunan Nusantara XIV Makassar - Fathirah, Dian; S, Masnawaty; Azis, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
This research aims: to determine the analysis of the application of value added tax at PT Perkebunan Nusantara XIV. The data collection methods used were interviews and documentation. The types and sources of data obtained are primary and secondary data, while the analysis method used is the comparative descriptive analysis method. Based on the research carried out, the results obtained from the analysis of PT Perkebunan Nusantara Value (VAT) and Sales Tax on Luxury Goods (PPnBM). The company's implementation of Value Added Tax is in accordance with Law Number 42 of 2009 concerning the Third Amendment to Law No. 8 of 1983 concerning Value Added and Services Tax and Sales Tax on Luxury Goods. So the author recommends that PT Perkebunan Nusantara XIV Makassar maintain its compliance and consistency in implementing value added tax.